Developing English Module for Seventh-Grade Students at MTs Al Hidayah Sukonolo: English - ERWINA DEWI SAFITRI Erwina; Tyas Alhim Mubarok; Istina Atul Makrifah (Journal of English Development, 2024)
This study focuses on helping English students and teachers find the ideal development module material for reading comprehension Under the 2013 curriculum, this study is a module that extends exercises to Help students understand English lessons and use the latest materials and resources. There are several reasons underlying this research, but (1) English language learning in this class applies a student center to discover students' interests and talents in the class, and the contextual method allows students to be proactive in following lessons. Research and Development (R&D), or research used to make certain goods and evaluate their suitability. This research and development use the ADDIE research model developed by Dick and Carry (1996). Media verification results of 90% and 8O by 5 performances from learning professionals. Product test results made in 2 meetings reached 74.0625%. The research and development results show a significant impact On the use of the reading module for students learning English. In conclusion, this module is an effective learning media that complements students' learning materials when studying English reading comprehension.